A double‐blind randomised feasibility trial of angiotensin‐2 in cardiac surgery*. (1st August 2022) - Coulson, T. G.; Miles, L. F.; Serpa Neto, A.; Pilcher, D.; Weinberg, L.; Landoni, G.; Zarbock, A.; Bellomo, R.
Summary: Acute kidney injury is common after cardiac surgery. Vasoplegic hypotension may contribute to kidney injury, and different vasopressors may have variable effects on kidney function. We conducted a double‐blind, randomised feasibility trial comparing peri‐operative angiotensin‐2 with noradrenaline. We randomly allocated 60 patients at two centres to a blinded equipotent angiotensin‐2 or noradrenaline infusion intra‐operatively and for up to 48 h postoperatively, titrated to mean arterial pressure of 70–80 mmHg. Primary feasibility outcomes included consent rate, protocol adherence, infusion duration, mean arterial pressure maintenance in the target range and major adverse outcomes. Secondary outcomes included kidney injury rate. The consent rate was 47%. Protocol adherence was 100% in the angiotensin‐2 group and 94% in the noradrenaline group. Study drug duration was median (IQR [range]) 217 (160–270 [30–315]) vs. 185 (135–301 [0–480]) min (p = 0.78) min intra‐operatively, and 5 (0–16 [0–48]) vs. 14.5 (4.8–29 [0–48]) hours (p = 0.075) postoperatively for angiotensin‐2 and noradrenaline, respectively. The mean arterial pressure target was achieved postoperatively in 25 of 28 (89%) of the angiotensin‐2 group and 27 of 32 (84%) of the noradrenaline group. One participant had a stroke, one required extracorporeal support and three required renal replacement therapy, all in the noradrenaline group (p = 0.99, p = 0.99 and p = 0.1). Acute kidney injury occurred in 7 of 28 in the angiotensin‐2 group vs. 12 of 32 patients in the noradrenaline group (p = 0.31). This pilot study suggests that a trial comparing angiotensin‐2 with noradrenaline is feasible. Its findings justify further investigations of angiotensin‐2 in cardiac surgery.